2000
DOI: 10.3354/meps198109
|View full text |Cite
|
Sign up to set email alerts
|

Are vertical distribution patterns of scleractinian corals maintained by pre- or post-settlement processes? A case study of three contrasting species

Abstract: ABSTRACT. Vertical zonation of hard corals in tropical coral reef Systems is a weil documented and predictable pattern in the organisation of tropical coral communities. However, the mechanisms that underly vertical zonation of hard corals are poorly understood. Two alternative conceptual models for the maintenance of vertical zonation are considered; depth-dependent settlement of larvae, or indiscriminant settlement of larvae with distnbutions determined by differential post-settlement mortality with depth. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
40
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 26 publications
4
40
0
Order By: Relevance
“…Resale or republication not permitted without written consent of the publisher coral planulae are primitive larvae with limited mobility and no specialized organs (Harrison & Wallace 1990) has led to the assumption that their dispersal and survival is a predominantly passive, stochastic process (Scheltema 1986, Garrison 1999, Mundy & Babcock 2000. However, recent studies have shown that coral planulae move both actively and passively during dispersal and exhibit complex larval behavior during settlement (Babcock & Mundy 1996, Raimondi & Morse 2000, Stake & Sammarco 2003.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Resale or republication not permitted without written consent of the publisher coral planulae are primitive larvae with limited mobility and no specialized organs (Harrison & Wallace 1990) has led to the assumption that their dispersal and survival is a predominantly passive, stochastic process (Scheltema 1986, Garrison 1999, Mundy & Babcock 2000. However, recent studies have shown that coral planulae move both actively and passively during dispersal and exhibit complex larval behavior during settlement (Babcock & Mundy 1996, Raimondi & Morse 2000, Stake & Sammarco 2003.…”
Section: Introductionmentioning
confidence: 99%
“…When considering larval behavior, one should be aware that life-history elements (i.e. growth, behavior and maintenance) are not independent, since energetic resources of invertebrate larvae are limited (Richmond 1987, Pechenik 1990, 1999, Hoegh-Guldberg & Emlet 1997, Bertram & Strathmann 1998, Pechenik et al 1998, Mundy & Babcock 2000. Differential allocation of resources among various life-history elements in response to variable environmental conditions provides the opportunity to optimize survival for an individual without means to replenish spent resources (Pechinek 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The location of adult conspecifics may be particularly important because larvae may choose to settle in areas where adults are abundant i.e. aggregative settlement (Mundy and Babcock 2000, Carlon 2002, Vermeij 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality during the first few months after settlement is generally very high in benthic marine invertebrates, including corals (Gosselin and Qian 1997;Mundy and Babcock 2000;Wilson and Harrison 2005). To date, however, there is little information for Acropora corals regarding the stage in the life history during which a difference in mortality between shallowand deep-habitat species can be observed.…”
Section: Introductionmentioning
confidence: 99%